Understanding of Religious Moderation in Buddhist Social Interaction - Citta Lokadhamma Santi; Naw Kham La Dhammasami (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2023)
The phenomenon of the life of the people of Karangsari Village who can live in harmony with each other for decades without seeing differences in beliefs, and without religious conflict is interesting to study. This study aims to describe and know the effect of understanding religious moderation on the social interaction of Buddhists in Karangsari village. This study uses a survey method using a quantitative approach. The results of the study can be concluded that the understanding of religious moderation affects the social interaction of Buddhists in Karangsari Village, Cluwak District, Pati Regency in 2022, namely the results of descriptive analysis of the understanding of the Religious Moderation variable showing a result of 82% including in the high category, while the social interaction variable shows a result of 79% belongs to the medium category. There is a significant influence between the understanding of religious moderation on social interaction, with a correlation value of 0.728 in the strong category. The coefficient of determination R Square is 0.530 so it can be interpreted that Understanding Religious Moderation contributes 53% to the social interaction of Buddhists in Karangsari Village. The results of the regression analysis in this study used the t-test with the results of t-count obtained at 4.504 with Sig. 0.000 ≤ 0.05 then H0 is rejected. Based on the results of these calculations, it can be assumed that the understanding of religious moderation has a significant effect on the social interaction of Buddhists in Karangsari Village, Cluwak District, Pati Regency in 2022.